2019
DOI: 10.1111/jace.16314
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of calcium aluminates at 60°C – Development paths of C2AHx in dependence on the content of free water

Abstract: The influence of water loss during the hydration of calcium aluminates on the phase development is investigated at 60°C. This is relevant for applications in which calcium aluminate cement (CAC) based formulations are exposed to quick drying during hydration. The presented results provide new insights into the well‐known conversion processes occurring in CAC pastes. Using in situ XRD two different routes of the development of initially formed C2AH8 are determined: (a) transformation to C3AH6 + AH3 in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This fact is disregarded in most reports in the literature. However, Hüller et al [155] and Goergens et al [77] recently demonstrated that a significant water loss might occur during in-situ XRD tests (illustrated in Figure 18), which is more marked as the temperature increases. For instance, at 23 °C (the testing temperature usually adopted), a mixing water loss of 10 wt% (around 3 wt% of the sample) was observed after 32 hours.…”
Section: Water Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact is disregarded in most reports in the literature. However, Hüller et al [155] and Goergens et al [77] recently demonstrated that a significant water loss might occur during in-situ XRD tests (illustrated in Figure 18), which is more marked as the temperature increases. For instance, at 23 °C (the testing temperature usually adopted), a mixing water loss of 10 wt% (around 3 wt% of the sample) was observed after 32 hours.…”
Section: Water Evaporationmentioning
confidence: 99%
“…Water loss over time for in-situ XRD measurements at different temperatures. (a) from [155], reproduced with permission from Wiley; (b) from [77], reproduced with permission from Elsevier.…”
Section: Water Evaporationmentioning
confidence: 99%